IMPLEMENTASI TEKNOLOGI DAN SAINS PADA SEKOLAH-PESANTREN BERBASIS ISLAM NUSANTARA - Sigit Tri Utomo (LP2M IAIN kUDUS, 2019)
Abstract:Education is an effort to create a superior generation and be able to compete in the global world. Because education is actually a process of changing one's paradigm of good thinking. Pendidina also able to change one's mindset so that they can explore themselves, therefore in Islamic educational institutions, especially Islamic-based Islamic boarding schools in the archipelago are needed in the development of technology and science.This research is a type of field research (fileld research), with a phenomenological approach. Data collection method in this study uses interviews with stakeholders in Islamic boarding schools based on the archipelago, not only that researchers also use observation methods related to the implementation of technology and science based on the archipelago of Islam, as well as documentation related to documents on the implementation of technology and science in Islamic schools archipelago-based Islam. In analyzing the data the researchers used data reduction and triangulation techniques to obtain accurate data related to the application of technology and science in Islamic-based Islamic boarding schools in the archipelago.